Coffee, including caffeinated and decaffeinated coffee, and the risk of hepatocellular carcinoma: a systematic review and dose–response meta-analysis. Issue 5 (9th May 2017) - Kennedy, Oliver John; Roderick, Paul; Buchanan, Ryan; Fallowfield, Jonathan Andrew; Hayes, Peter Clive; Parkes, Julie
Abstract : Objectives: To examine the association between coffee, including caffeinated and decaffeinated coffee, with hepatocellular carcinoma (HCC) and assess the influence of HCC aetiology and pre-existing liver disease. Design: We performed a systematic review and meta-analysis. We calculated relative risks (RRs) of HCC according to caffeinated and decaffeinated coffee consumption using a random-effects dose–response meta-analysis. We tested for modification of the effect estimate by HCC aetiology and pre-existing liver disease. We judged the quality of evidence using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Results: We found 18 cohorts, involving 2 272 642 participants and 2905 cases, and 8 case–control studies, involving 1825 cases and 4652 controls. An extra two cups per day of coffee was associated with a 35% reduction in the risk of HCC (RR 0.65, 95% CI 0.59 to 0.72). The inverse association was weaker for cohorts (RR 0.71, 95% CI 0.65 to 0.77), which were generally of higher quality than case–control studies (RR 0.53, 95% CI 0.41 to 0.69). There was evidence that the association was not significantly altered by stage of liver disease or the presence/absence of high alcohol consumption, high body mass index, type 2 diabetes mellitus, smoking, or hepatitis B and C viruses. An extra two cups of caffeinated and decaffeinated coffee (2 and 3 cohort studies, respectively) were associated with reductions of 27% (RR 0.73, 95% CI 0.63 to 0.85) and 14% (RR 0.86, 95% CI 0.74 to 1.00) in the risk of HCC. However, due to a lack of randomised controlled trials, potential publication bias and there being no accepted definition of coffee, the quality of evidence under the GRADE criteria was 'very low'. Conclusions: Increased consumption of caffeinated coffee and, to a lesser extent, decaffeinated coffee are associated with reduced risk of HCC, including in pre-existing liver disease. These findings are important given the increasing incidence of HCC globally and its poor prognosis.